An Analysis of Teachers Educational Role in Developing Religious Character Among Lower Grade Students - Primandini, Kirana; Sunarso, Ali (JTP - Jurnal Teknologi Pendidikan, 2025)
Religious character is a fundamental value that must be instilled in students as the foundation for a nation's progress. This study aims to analyze and identify the role of teachers and the indicators of their success in shaping the religious character of lower-grade students. This study used a descriptive qualitative approach, with the research subjects including 4 teachers. Data were collected through observation, interviews, and documentation. To ensure data validity, this study applies triangulation techniques. The data analysis process consists of data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the role of teachers in developing the religious character of low-grade students includes three main aspects as educators, mentors, and guides. As educators, teachers encourage students to develop positive habits. As mentors, they provide guidance in spiritual and religious aspects. Meanwhile, as guides, teachers play a crucial role in instilling moral values such as honesty, discipline, and tolerance. The indicators of success are reflected in the positive changes observed in students and the increase in religious practices. Changes in behavior, as well as improvements in worship are monitored through worship journals and memorization journals provided by the school as a form of evaluation that continues to be carried out to date. The implications of this study show that the importance of the teacher's role in shaping students' religious character, which has an impact not only in the classroom but also on education policy.